Efektivitas Model Pembelajaran T Efektivitas Model Pembelajaran Teams games Tournament secara Berdiferensiasi dengan Teaching at The Right Level terhadap pengaruh Hasil Belajar Siswa Kelas VIII Materi Unsur Senyawa Campuran: Model Pembelajaran Teams games Tournament secara Berdiferensiasi dengan Teaching at The Right Level - Aflah, Naufal Syafa; Supardi, Zainul Arifin Imam; Alima, Suci (PendIPA Journal of Science Education, 2024)
This research aimed to determine the effectiveness of the Teams games Tournament (TGT) learning model with a differentiated approach with the TGT Teaching at The Right Level (TaRl) approach to student learning outcomes of Elements, Compounds and Mixtures. This type of research is Classroom Action Research. Research subjects using 1 class VIII SMP were 34 students at SMP Negeri 26 Surabaya. Classroom Action Research by conducting observations and giving Pre-Test and Post-Test questions to students in science learning. In this study, 4 cycles were used, each cycle was carried out in 1 meeting. Cycle 1 and cycle 2 were carried out using a differentiated approach, while cycle 3 and cycle 4 were carried out using TaRl. In the first and third cycles, cognitive diagnostic assessments were carried out by giving pre-tests to students. Based on the results of this research, it was concluded that the TGT learning model activities with the TaRl approach had an influence on increasing student learning outcomes with a level of effectiveness dominated by the Quite Effective criterion of 61%. In fact, the difference in achievement of TGT effectiveness values ​​with a differentiated approach is very significant at 48%. This can be used as a reference for the importance of providing facilities such as learning approaches for students to obtain optimal learning results.